Application of Technology Adoption Through Value Co-Creation in UT Connect Marketing Program - Nugraha, Raditya Dwi; Marsasi, Endy Gunanto (Sekolah Tinggi Manajemen IPMI, 2023)
Researchers examined a company engaged in the heavy equipment industry where some marketing has been through digital. This study aims to evaluate the marketing used by companies regarding UT Connect marketing media and UT clicks to support online sales of company products and make it easier for users to access available systems. The study used descriptive qualitative research with observation, in-depth interviews, secondary company data, and documentation collection. This research resulted in an evaluation of UT Connect and UT click to facilitate information transactions to online purchases using the theory of Technology Adoption with the concept of Value Co-Creation, which will be implemented to support the marketing media of PT. United Tractors Tbk in the evaluation of a program called UT Connect.